Composition of fatty acids in hemp leaves (Cannabis sativa L.) under the impact of aphids and a herbicide - Roma Durak; Beata Borowiak-Sobkowiak; Ewa Szpyrka; Tomasz Durak; Beata Ciak; Małgorzata Jedryczka (Journal of Plant Protection Research, 2025)
Cannabis aphid Phorodon (Diphorodon) cannabis Passerini 1860 is an economically important pest of oil hemp (Cannabis sativa L.) and is controlled by insecticides. Oil hemp crops are treated with herbicides, which are non-target pesticides for aphids but may also affect aphid populations. Such ecological implications of plant protection products are rarely investigated. The aim of the present research was to better understand plant ‒ aphid ‒ herbicide interactions, specifically, changes of fatty acids (FAs) in leaves, caused by cannabis aphids and a common herbicide used in hemp fields. Of 21 FAs detected in hemp leaves, aphid feeding significantly increased the amounts of myristic and oleic acids and decreased the content of α-linolenic acid. This effect was found when aphids fed on hemp plants and especially when plants were treated with an herbicide containing quizalofop-P-tefuryl. This compound on its own did not affect the FA composition. In spite of the extremely high increase of myristic acid (7- to 9-fold, depending on the experiment variant), which could cause the repellent effect in hemp plants, the decreased amount of α-linolenic acid, the precursor of jasmonic acid may have helped aphids to manipulate the jasmonate signaling pathway involved in plant defense to herbivory enabling their continued feeding on hemp. This study revealed the importance of FAs in plant defense as well as the side effects of non-target plant protection products. Future pest management should take into account the complex interactions between crop plants, their pests and non-target effects of chemicals used in real field situations.